MODIFICATION OF TENNIS BALLS ON SHOT PUT - Ahmad Lamusu (Universitas Negeri Gorontalo, 2020)
This study aims to improve learning outcomes Reject Bullets through learning tools for modification of tennis balls for VII grade students of SMP Negeri I Telaga by using learning media for modifying tennis balls. This research is a classroom action research (CAR) consisting of two cycles and each cycle consists of three meetings. From the results of data analysis, the average student learning outcomes in how to hold a bullet, put a bullet and reject a bullet has increased. While 1 student did not reach the minimum completeness criteria set by the school, but it was already included in the sufficient criteria in Shot Put learning. This study proves that if a tennis ball modification is applied, the learning outcomes of Grade VII Bullet Resistant students of SMP Negeri I Telaga Gorontalo Regency have increased.